(NmETOD TRIGONOMETRI^ESKIH SUMM W TEORII ^ISEL (B/s - (NwINOGRADOW(B, (Ni(B.(Nm(B.s ((NmOSKWA (B:s (NnAUKA(B. (NgL(B. (NRED(B. (NFIZ(B.-(NMAT(B. (NLIT(B.,s, 1980)
(NbIBLIOGR(B.: (NS (B159(16 (NNAZW(B.)s
Keywords: (NmETOD TRIGONOMETRI^ESKIH SUMMs; (NtEORIQ ^ISELs